Neuromorphic Computing Using NAND Flash Memory Architecture With Pulse Width Modulation Scheme - Lee, Sung-Tae; Lee, Jong-Ho (Frontiers in Neuroscience, 2020)
A novel operation scheme is proposed for high-density and highly robust neuromorphic computing based on NAND flash memory architecture. Analog input is represented with time-encoded input pulse by pulse width modulation (PWM) circuit, and 4-bit synaptic weight is represented with adjustable conductance of NAND cells. Pulse width modulation scheme for analog input value and proposed operation scheme is suitably applicable to the conventional NAND flash architecture to implement a neuromorphic system without additional change of memory architecture. Saturated current-voltage characteristic of NAND cells eliminates the effect of serial resistance of adjacent cells where a pass bias is applied in a synaptic string and IR drop of metal wire resistance. Multiply–accumulate (MAC) operation of 4-bit weight and width-modulated input can be performed in a single input step without additional logic operation. Furthermore, the effect of quantization training (QT) on the classification accuracy is investigated compared with post-training quantization (PTQ) with 4-bit weight. Lastly, a sufficiently low current variance of NAND cells obtained by the read–verify–write (RVW) scheme achieves satisfying accuracies of 98.14 and 89.6% for the MNIST and CIFAR10 images, respectively.